Impact of the menstrual cycle phases and time of day on markers of stress: salivary α-amylase and secretory immunoglobulin A - Josey K. Walker; Courtney C. Dillard; Drew E. Gonzalez; Hunter S. Waldman; Matthew J. McAllister (Stress)
Previous reports suggest that the menstrual cycle (MC) phases can impact cortisol concentrations. However, research is needed on whether the MC impacts other markers of stress and immune function. It has also been shown that some biomarkers are impacted by time of day, although differences between morning (AM) and afternoon (PM) biomarkers have not been studied over the course of the MC. This study assessed the effect of MC phases and time of day on salivary stress biomarkers [salivary α-amylase (sAA), secretory immunoglobulin A (SIgA)], progesterone, resting blood pressure and resting heart rate (RHR). A single-group repeated measure design was employed in which seventeen participants (n = 17) monitored their MC for two months while attending eight experimental sessions which included both AM and PM sessions during each predicted 1) menses, 2) follicular, 3) ovulatory and 4) luteal phases. Resting blood pressures, heart rates, body composition parameters (assessed via bioelectrical impedance analysis), sAA and SIgA concentrations were assessed. No time of day x MC phase interactions (p > 0.05) were noted for sAA or SIgA, resting blood pressure, heart rate, or body composition parameters. However, sAA and RHR were significantly higher in the PM, while SIgA was significantly higher in the AM. These data suggest that the MC phases do not impact sAA or SIgA, resting blood pressure, heart rates, or body composition parameters. However, time-of-day impacts RHR and concentrations of sAA and SIgA. These findings provide implications for female participants in research dealing with these biomarkers.